Effects of After-School Volleyball Program on Body Composition in Overweight Adolescent Girls - Nebojša Trajković; Anja Lazić; Drena Trkulja-Petković; Valentin Barišić; Vladan Milić; Siniša Nikolić; Goran Sporiš (MDPI AG, 2021)
The current study aimed to investigate the effects of an after-school volleyball program on body composition in overweight adolescent girls. Forty-two girls were randomly divided into a volleyball group (VG) (n = 22 age: 15.6 ± 0.5 years) and control group (CG) (n = 20; age: 15.5 ± 0.7 years). Both groups continued with their usual physical education activities, while VG was included as small-sided games, two times a week, after school, on modified volleyball courts. Body mass, body mass index (BMI), body fat in kg, body fat percentage, and muscle mass were analyzed by a bioelectrical impedance method. There was a significant interaction of group (VG vs. CG) × time (pre-vs. post) for weight [F1, 40 = 7.933; p = 0.004] and BMI [F1, 40 = 5.764; p = 0.015]. Additionally, a significant main effect of time was found for body fat (kg) [F1, 40 = 17.650; p < 0.001] and body fat (%) [F1, 40 = 18.721; p < 0.001]. The results of the current study show that a twelve-week after-school volleyball program, including two sessions a week, can improve body composition in overweight adolescent girls.